Microbial Ecology of Atlantic Salmon (Salmo salar) Hatcheries: Impacts of the Built Environment on Fish Mucosal Microbiota - Minich, Jeremiah J. (Appl Environ Microbiol, 2020)
Successful rearing of fish in hatcheries is critical for conservation, recreational fishing, commercial fishing through wild stock enhancements, and aquaculture production. Flowthrough (FT) hatcheries require more water than recirculating aquaculture systems (RAS), which enable up to 99% of their water to be recycled, thus significantly reducing environmental impacts. Here, we evaluated the biological and physical microbiome interactions of three Atlantic salmon hatcheries (RAS n = 2, FT n = 1). Gill, skin, and digesta from six juvenile fish along with tank biofilms and water were sampled from tanks in each of the hatcheries (60 fish across 10 tanks) to assess the built environment and mucosal microbiota using 16S rRNA gene sequencing. The water and tank biofilm had more microbial richness than fish mucus, while skin and digesta from RAS fish had 2 times the richness of FT fish. Body sites each had unique microbiomes (P < 0.001) and were influenced by hatchery system type (P < 0.001), with RAS being more similar. A strong association between the tank and fish microbiome was observed. Water and tank biofilm richness was positively correlated with skin and digesta richness. Strikingly, the gill, skin, and digesta communities were more similar to that in the origin tank biofilm than those in all other experimental tanks, suggesting that the tank biofilm has a direct influence on fish-associated microbial communities. Lastly, microbial diversity and mucous cell density were positively associated with fish growth and length. The results from this study provide evidence for a link between the tank microbiome and the fish microbiome, with the skin microbiome as an important intermediate. IMPORTANCE Atlantic salmon, Salmo salar, is the most farmed marine fish worldwide, with an annual production of 2,248 million metric tons in 2016. Salmon hatcheries are increasingly changing from flowthrough toward recirculating aquaculture system (RAS) design to accommodate more control over production along with improved environmental sustainability due to lower impacts on water consumption. To date, microbiome studies of hatcheries have focused either on the fish mucosal microbiota or on the built environment microbiota but have not combined the two to understand their interactions. Our study evaluates how the water and tank biofilm microbiota influences the fish microbiota across three mucosal environments (gill, skin, and digesta). Results from this study highlight how the built environment is a unique source of microbes to colonize fish mucus and, furthermore, how this can influence fish health. Further studies can use this knowledge to engineer built environments to modulate fish microbiota for beneficial phenotypes.